Analisis Distribusi Dan Hubungan Regresi Antara Parameter Pada Sistem Jaringan Irigasi Perforasi - I Dewa Gede Jaya Negara Negara; Agus Suroso; Anid Supriyadi; Heri Sulistiyono; Lalu Muhamad Dicko Febriza (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
The diversity of dryland topography, such as flat land, sloping land, and even steep slopes, often becomes an obstacle in the development of agricultural businesses. One of these obstacles is the limited water sources and the method of providing water in appropriate agricultural development. Currently, many irrigation systems have been developed, but the sprinkler irrigation system with perforated pipes is still very rarely used in the field. The perforated irrigation system is an irrigation system with perforated pipes, where water pressure is used as energy to emit water to the land in one or two land lines. This perforated irrigation test aims to determine the effect of variations in the length of the perforated pipe and variations in the head on the distribution of irrigation in the lateral pipe and in each perforation hole in the lateral pipe and to find the regression relationship of these parameters. This perforated pipe irrigation system test used three lateral pipes with a distance between the pipes of 1 m and a water tank height of approximately 3 meters with a capacity of ± 200 liters. The test was carried out on three variations in the length of the lateral pipe, namely L1 = 4 meters, L2 = 5 meters, and L3 = 6 meters with a diameter of 1/2 inch, the distance between the perforation holes is 60 cm. Meanwhile, the variations in the test head heights consisted of h1 = 350 cm, h2 = 360 cm, h3 = 370 cm, and h4 = 380 cm. The results showed that irrigation distribution was more stable at lengths L1 and L2, and the larger the head, the smaller the average irrigation deviation. There was a decrease in irrigation distribution of 23.33 ml for every 60 cm increase in perforated pipe length. In general, the regression relationship between irrigation yield and the position of the perforated pipe holes is polynomial regression